Genetic Characterization of the Thymidine Kinase of Koi Herpesvirus 3 in Sulaymaniyah Province, Iraq - Abdulrahman, Nasreen M.; Abid, Omed I.; Sleman, Sirwan; Baba Sheikh, Mohammed O.; Rashid, Peshnyar M.A.; Abass, Zaniar A. (Iraqi Journal of Science, 2024)
Koi herpesvirus 3 (KHV-3) is nominated as an emerging, highly devastating, and contagious viral disease with severe economic losses in the carp aquaculture industries worldwide. Carp rearing under intensive culture conditions is constantly vulnerable to infection by various pathogens in the water. Water temperature has a major influence on the onset and severity of the disease. Since common carp have gained importance in the Iraqi fish industry, the investigation and control of associated diseases, including KHV, are warranted. We confirmed the first detection of the KHV from the collected specimens from the suspected cages in the Sulaymaniyah region. Also, an analysis of the thymidine kinase (TK) gene sequence of the KHV showed that the virus strain had a point mutation (proline, P193) instead of threonine, T193. The isolated KHV strains were subdivided into three clades with three distinct genotypes: Asian (Iranian, Indonesian, Japanese, and Chinese), European (UK), and North American (USA and Mexico) genotypes. The virus sequences were more closely related to the Iranian and Indonesian genotypes. This report describes the first isolation and genetic characterization of koi herpesvirus (KHV) in the Sulaymaniyah province, which is important for efficacious management and vaccination programs in the future to control KHV infection in carp cages in Northern Iraq.